Spectrum and antifungal susceptibility of Candida and Cryptococcus species isolated from HIV-positive patients in a tertiary care center in North India - Kumari, Nirmala; Malhotra, Shalini; Kumar Chauhan, Ankit; Kaur, Nirmaljeet; Duggal, Nandini (International Journal of Research in Medical Sciences, 2026)
Background: In people with HIV, opportunistic fungal infections are a leading cause of morbidity and death. Local data on pathogen distribution and antifungal resistance guide clinical management. Methods: A cross-sectional study was conducted (November 2019–March 2021) among 200 HIV-positive adults with suspected fungal infection at a tertiary care hospital in New Delhi, India. A total of 323 clinical specimens were collected, including oral swabs, blood, urine, sputum, and cerebrospinal fluid (CSF). Yeasts were identified by microscopy, germ tube test, chromogenic agar, and automated ID systems. Antifungal susceptibility was evaluated using Etest and CLSI microbroth dilution methods. Results: Of 323 specimens, 89 (27.5%) were culture positive. Candida species predominated in oral swabs (38/39, 97.4%) and sputum (18/23, 78.3%), while Cryptococcus neoformans was isolated from 15/15 culture-positive CSF samples. Among 67 Candida isolates, resistance to fluconazole was 14.9% (10/67), itraconazole 9.0% (6/67), and voriconazole 3.0% (2/67); all were susceptible to amphotericin B. MIC50/90 values for C. albicans were 0.25/0.5 µg/ml (fluconazole) and 0.5/1 µg/ml (amphotericin B). Sixteen C. neoformans isolates were fully susceptible to voriconazole, fluconazole, itraconazole, and amphotericin B. Conclusions: In this HIV cohort, mucosal and airway candidiasis predominated, while C. neoformans was the leading CSF pathogen. Fluconazole resistance in Candida was non-trivial, underscoring the need for susceptibility-guided therapy. Universal susceptibility among C. neoformans is reassuring. Regular surveillance is essential to guide empiric antifungal use and stewardship.